Brief electrical stimulation after facial nerve transection and neurorrhaphy: a randomized prospective animal study. Issue 1 (December 2016) - Mendez, Adrian; Seikaly, Hadi; Biron, Vincent; Zhu, Lin; Côté, David
Abstract Background Recent studies have examined the effects of brief electrical stimulation (BES) on nerve regeneration, with some suggesting that BES accelerates facial nerve recovery. However, the facial nerve outcome measurement in these studies has not been precise or accurate. The objective of this study is to assess the effect of BES on accelerating facial nerve functional recovery from a transection injury in the rat model. Methods A prospective randomized animal study using a rat model was performed. Two groups of 9 rats underwent facial nerve surgery. Both group 1 and 2 underwent facial nerve transection and repair at the main trunk of the nerve, with group 2 additionally receiving BES on post-operative day 0 for 1 h using an implantable stimulation device. Primary outcome was measured using a laser curtain model, which measured amplitude of whisking at 2, 4, and 6 weeks post-operatively. Results At week 2, the average amplitude observed for group 1 was 4.4°. Showing a statistically significant improvement over group 1, the group 2 mean was 14.0° at 2 weeks post-operatively (p = 0.0004). At week 4, group 1 showed improvement having an average of 9.7°, while group 2 remained relatively unchanged with an average of 12.8°. Group 1 had an average amplitude of 13.63° at 6-weeks from surgery. Group 2 had a similar increase in amplitude with an average of 15.8°. There was no statistically significant difference between the two groups at 4 and 6 weeks after facial nerve surgery. Conclusions This is the first study to use an implantable stimulator for serial BES following neurorrhaphy in a validated animal model. Results suggest performing BES after facial nerve transection and neurorrhaphy at the main trunk of the facial nerve is associated with accelerated whisker movement in a rat model compared with a control group.